Unheard Narratives of Public-School Teachers’ Coffee Consumption - Polinar, Mark Anthony N.; Mahipos, April Marie N.; Rabanes, Bertella G.; Flores, Imie Jasmin L. (Transpublika Publisher, 2024)
Teachers have a pivotal role in shaping students’ intellect by sharing knowledge and fostering critical thinking. Despite being perceived as resilient, they encounter struggles that impede their effectiveness due to overwhelming paperwork, classroom management issues, administrative responsibilities, and the nature of their work. As a result, one of the ways they cope to alleviate stress is by turning to coffee and making it a part of their routine. This phenomenology study explored the unheard narratives of public-school teachers’ frequency of coffee consumption, motivation, and impact on their daily routine. Ten (10) key informants were selected using purposive sampling to participate in the study. A structured interview guide was used and executed in a Focus Group Discussion (FGD) as an approach to data collection. The study revealed that the aroma, antioxidants, and warm feelings were the themes that drove teachers to consume coffee. Also, coffee provides an extra boost of energy, a brighter mood, and a sense of fulfillment as it is perceived to contribute to the daily routine of teachers. It is concluded that coffee secures a spot in the daily habits of teachers as it gives them the alertness and activeness needed to begin their day effectively. In addition, taking coffee breaks allows teachers to discuss their issues and difficulties while offering each other support. This fosters a sense of camaraderie over a cup of coffee, potentially resulting in solid friendships and forming a tight-knit teaching community, all for the benefit of the students.